Stevens-Johnsons syndrome and toxic epidermal necrolysis: A case report - Subba, H K; Adhikari, S; Subba, R (Journal of Chitwan Medical College, 2017)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are serious systemic disorders in which there are vesicobullous lesions involving the skin and mucous membranes, most commonly triggered by medications. It is a potentially fatal condition that damages multiple organs. A 22 years male patient admitted with the complaint of sudden appearance of blisters first over oral cavity after taking Ibuprofen. He developed generalized macular lesions over trunk, chest, face and lower limbs. He was treated with steroid, antibiotics and conservative management.